Zulfiyakhanim: Life And Creative Works - Ahmadova Mubinabonu Oybekovna (Next Scientists International Journal JSSHRF, 2026)
This article presents a scholarly analysis of the life and creative work of the renowned Uzbek poet Zulfiyakhanim, examining the influence of her personal development, inner world, and social engagement on her literary output. The study explores her childhood and adolescence, family and social environment, life experiences, and how these factors shaped her literary career. Furthermore, the article discusses the significance of Zulfiyakhanim’s works for younger generations, particularly adolescents, in terms of psychological well-being, personal development, and moral education.